Cognitive impairment and associated factors among institutionalized elderly persons in Natal, Rio Grande do Norte, Brazil - Andrade,Fabienne Louise Juvêncio Paes de (2017)
Abstract Objective: To identify the prevalence of cognitive impairment and associated factors among institutionalized elderly persons. Methods: A cross-sectional study was conducted from October to December 2013 in Long-Term Care Facilities for the elderly in Natal, Rio Grande do Norte, Brazil, featuring 326 elderly persons of both genders. The assessment of cognitive decline was classified using the Pfeiffer test. Information on sociodemographic conditions and health status was also recorded. Nutritional status was assessed by applying the Mini Nutritional Assessment tool and functional capacity with the Katz Index. To identify the factors associated with the presence of moderate or severe cognitive impairment multiple logistic regression analysis of variables with a p value >0.20 was performed, using the Stepwise Forward method. Results: It was observed that 83.6% (95% CI: 78.9 to 87.3%) of the elderly persons had cognitive impairment. The final model, adjusted for type of LTCF, showed that being 83 years old or older was considered a risk factor for moderate or severe cognitive impairment. However, having systemic arterial hypertension (SAH) and having been institutionalized through their own choice were considered protective factors for moderate or severe cognitive impairment. Conclusion: the variables age, having SAH and having been institutionalized through their own choice are directly associated, as risk or protection factors, with the presence of severe or moderate cognitive impairment of the elderly population. The early diagnosis of these factors can lead to greater focus in setting goals for prevention and health care, thus improving the quality of life of these individuals.